2022
DOI: 10.1155/2022/4347753
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Testing on Mechanical, Durability, and Adsorption Dispersion Properties of Concrete with Multiwalled Carbon Nanotubes and Silica Fumes

Abstract: The major goal of this research is to see how carbon nanotubes and silica fume affect the durability and mechanical qualities of high-performance concrete (HPC). Mechanical properties, such as split tensile strength, compressive strength, elasticity modulus, and flexural strength, and durability properties like water absorption, abrasion, chloride penetration, acid, and sea water resistance, impact resistance of HPC consisting silica fume (SF), and carbon nanotubes (CNT) were examined in this study. Varied tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The increase in the adsorbing agent dosage results in increased contact with the adsorbing surface due to the rise in the chemical interactions with the active zones until a certain threshold where the adsorption rate rises [ 49 ]. The influence of adsorbent dosage in the adsorption of Pb ions by peanut shell biochars is presented in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the adsorbing agent dosage results in increased contact with the adsorbing surface due to the rise in the chemical interactions with the active zones until a certain threshold where the adsorption rate rises [ 49 ]. The influence of adsorbent dosage in the adsorption of Pb ions by peanut shell biochars is presented in Figure 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Liew et al [29] indicated that because of their nanoscale size, CNT and other nanomaterials can impede the spread of microcracks in concrete. In their experimental studies comparing separately the outcomes of concrete prepared with CNT and silica fume, Chukka et al [30] found that CNT-infused concrete performed better than conventional and silica fume-mixed concrete Additionally, Dietzel et al [31] demonstrated that single-walled CNTs' mechanical characteristics are remarkable when compared to typical conventional fbres. Similar to single-walled CNTs, MWCNT inclusion to improve the toughness and mechanical properties when combined with cement has been the focus of various studies.…”
Section: Use Of Cnt and Mwcntmentioning
confidence: 99%
“…High compressive strength in concrete shows a hard nature, moisture resistant tendency, and the resisting tendency to other external forces. The quality of concrete can be assured through the determination of compressive strength [7,8]. The workability of fresh concrete gives an idea of the frictional behavior of the concrete from the time it is mixed to the time it is compacted.…”
Section: Introductionmentioning
confidence: 99%